The State of Economic and Social Human Rights 2013
DOI: 10.1017/cbo9781139235600.016
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Environmental Human Rights: A Descriptive Analysis of 142 National Constitutions

Abstract: I thank Amy Jeffords for her love and support, and for helpful editing. I thank Lanse Minkler and Shareen Hertel for helpful comments and suggestions that led to improvements in this paper. I also thank Joshua Berning and participants at the 2011 Economics and Social Rights Group Workshop for thoughtful discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…The primary independent variables of interest are (1) the presence of a CER, and (2) a simple measure of the legal strength of a given CER based on its language. These data come from Jeffords (2013), where the first is operationalized by a simple indicator variable noting whether a constitution has a CER provision (denoted by a "1") or does not (denoted by a "0"), and the second specification is an additive index of seven keyword categories. Jeffords (2013) examined the constitutions of 198 countries as of 2010 for instances of CER provisions and found that 125 constitutions contain a uniquely written provision.…”
Section: Iii2 Primary Independent Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary independent variables of interest are (1) the presence of a CER, and (2) a simple measure of the legal strength of a given CER based on its language. These data come from Jeffords (2013), where the first is operationalized by a simple indicator variable noting whether a constitution has a CER provision (denoted by a "1") or does not (denoted by a "0"), and the second specification is an additive index of seven keyword categories. Jeffords (2013) examined the constitutions of 198 countries as of 2010 for instances of CER provisions and found that 125 constitutions contain a uniquely written provision.…”
Section: Iii2 Primary Independent Variablesmentioning
confidence: 99%
“…These data come from Jeffords (2013), where the first is operationalized by a simple indicator variable noting whether a constitution has a CER provision (denoted by a "1") or does not (denoted by a "0"), and the second specification is an additive index of seven keyword categories. Jeffords (2013) examined the constitutions of 198 countries as of 2010 for instances of CER provisions and found that 125 constitutions contain a uniquely written provision. 17 Each provision was then examined for the presence of seven keyword categories endemic to the literature that defines and outlines ERs.…”
Section: Iii2 Primary Independent Variablesmentioning
confidence: 99%
See 3 more Smart Citations